Desistance: The "other side" of change and implications for maintenance programs. Issue 7 (2nd October 2016) - Youssef, Carollyne; Casey, Sharon; Day, Andrew
ABSTRACT: How offenders cease offending and engage in the desistance process is a key consideration for effective rehabilitation. While attention is increasing on desistance and its utility in the supervision and case management of offenders postrelease, it's yet to be integral to postrelease programs. This paper considers the implications of the desistance process for psychological postrelease programs, such as community maintenance programs. There will be a brief review of some of the theories of desistance, consideration of the interrelationship between desistance theory and community maintenance programs and discussion about the implications of desistance theory for the delivery of community maintenance programs.